2017
DOI: 10.1039/c6sc05021b
|View full text |Cite
|
Sign up to set email alerts
|

Highly near-IR emissive ytterbium(iii) complexes with unprecedented quantum yields

Abstract: We report a series of highly NIR emissive Yb complexes, in which the Yb is sandwiched between an octafluorinated porphyrinate antenna ligand and a deuterated Kläui ligand, and one of the complexes has an unprecedented quantum yield of 63%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 79 publications
5
95
0
Order By: Relevance
“…The efficiency of NIR OLEDs is currently limited by the low PLQY of lanthanide complexes, since the NIR transition could be deactivated even by C–H vibration. In recent years, some work demonstrated that the luminescence efficiency of NIR lanthanide complexes could be greatly improved by using deuterated and fluorinated ligands . This strategy even suits for the lanthanide which has scattered spectrum to enhance the emission efficiency of visible light .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The efficiency of NIR OLEDs is currently limited by the low PLQY of lanthanide complexes, since the NIR transition could be deactivated even by C–H vibration. In recent years, some work demonstrated that the luminescence efficiency of NIR lanthanide complexes could be greatly improved by using deuterated and fluorinated ligands . This strategy even suits for the lanthanide which has scattered spectrum to enhance the emission efficiency of visible light .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…4 Similarly, for an organic solar cell (OSC) k fl and k nr determine the exciton lifetime and thereby the probability that an exciton generates charge carriers. 5 These k nr 's are important in many other fields, including: phosphorescent OLEDs, [6][7][8] biomedical labeling, [9][10][11] photodynamic therapy, 12-14 laser dyes, [15][16][17] and luminescent solar concentrators. [18][19][20] In reality, the prediction of quantum yields (Φ) has been very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Organic dyes and complexes 9 have long been employed as sensitizing agents for Ln ion transitions, with photoluminescent quantum yields (PLQYs)of 75% being reported. 10 Though the absorption of the Ln ions is improved with these materials, they still do not offer a broad band absorption profile or the level of control that is necessary for achieving very high (>95%) PLQYs. Due to the lack of a protective shell in the materials, nonradiative quenching processes are present and can have a large impact on the PLQY of the material.…”
Section: Introductionmentioning
confidence: 99%